Bioactive substance contents and antioxidant capacity of the lipid fraction of Annona crassiflora Mart. seeds - Luzia, Débora M.M. [UNESP]; Jorge, Neuza [UNESP] (Elsevier, 2013)
Annona crassiflora Mart. is a typical fruit of the Brazilian cerrado, considered to be a species of economic interest, mainly for its use in cooking, which is widespread among the inhabitants of that region, and can be found in many typical local dishes, especially sweets, jellies, liqueurs, soft drinks, ice creams and juices. Thus, the objective of this study was to determine the bioactive substance contents and the antioxidant capacity of the lipid fraction of A. crassiflora Mart. seeds in the interest of better identifying the quality of this raw material from the Brazilian cerrado. After the receipt of the fruits, the seeds were removed manually and, then, the lipid fraction was obtained by cold extraction with chloroform:methanol:water (2:1:0.8, v/v/v) and analyzed for the composition of phytosterols, tocopherols, fatty acids, total carotenoids, antioxidant activity and oxidative stability index. The lipid fraction showed significant quantity of bioactive substances, especially phytosterols, tocopherols and unsaturated fatty acids, as well as significant antioxidant capacity and oxidative stability, influenced by the content of phytosterols and the composition of fatty acids present in the analyzed fraction. © 2012 Elsevier B.V.
Keywords: Antioxidants; Araticum; Bioactives; Extraction; Fruits; Vegetable oils; Antioxidant activities; Antioxidant capacity; Bioactive substances; Brazilian cerrado; Economic interests; Ice creams; Lipid fractions; Oxidative stability; Oxidative stability index; Soft drinks; Total carotenoids; Agents; Beverages; Methanol; Oxidation resistance; Thermal processing (foods); Unsaturated fatty acids; Pigments; antioxidant; bioactivity; cerrado; chloroform; fruit; lipid; qualitative analysis; seed; vegetable oil; Brazil; Annona; Annona crassiflora